Health and Safety Considerations of Fermented Sausages - Askild Holck; Lars Axelsson; Anette McLeod; Tone Mari Rode; Even Heir (Journal of Food Quality)
Fermented sausages are highly treasured traditional foods. A large number of distinct sausages with different properties are produced using widely different recipes and manufacturing processes. Over the last years, eating fermented sausages has been associated with potential health hazards due to their high contents of saturated fats, high NaCl content, presence of nitrite and its degradation products such as nitrosamines, and use of smoking which can lead to formation of toxic compounds such as polycyclic aromatic hydrocarbons. Here we review the recent literature regarding possible health effects of the ingredients used in fermented sausages. We also go through attempts to improve the sausages by lowering the content of saturated fats by replacing them with unsaturated fats, reducing the NaCl concentration by partly replacing it with KCl, and the use of selected starter cultures with desirable properties. In addition, we review the food pathogenic microorganisms relevant for fermented sausages (Escherichia coli, Salmonella enterica, Staphylococcus aureus, Listeria monocytogenes, Clostridium botulinum, and Toxoplasma gondii) and processing and postprocessing strategies to inhibit their growth and reduce their presence in the products.